Impact of Adoption of Directly Measured Low-Density Lipoprotein-Cholesterol (LDL-C) on Targets of Lipid Control and Its Comparison With Friedewald Formula-Calculated LDL Cholesterol in People With Type-2 Diabetes Mellitus. Issue 3 (September 2021) - Jagesh, Rejitha; John, Mathew; Jalaja, Manju Manoharan Nair; Oommen, Tittu; Gopinath, Deepa
Objectives: The accurate and precise measurement of low-density lipoprotein-cholesterol (LDL-C) is important in the assessment of atherosclerotic cardiovascular disease risk (ASCVD) in people with diabetes mellitus. This study is aimed at comparing directly measured LDL-C with Friedewald formula (FF)-calculated LDL-C (c-LDL-C) in people with type-2 diabetes. Methods: Fasting lipid profiles of 1905 people with type-2 diabetes, whose LDL-C was estimated by direct LDL assay, were chosen for the study. In the same group, LDL-C was calculated with FF. Correlation and agreement between these methods were analyzed at various strata of triglycerides (TGs). The possibility of misclassifying people at various levels of LDL-C targets proposed in literature was calculated. Results: The mean LDL-C levels were lower in the c-LDL-C group across various TG strata. A significant correlation was found between c-LDL-C and direct LDL-C for all the study samples ( r = 0.948, P < .001) and across all TG strata. Analysis of agreement showed a positive bias for direct LDL-C which increased at higher strata of TGs. c-LDL-C underestimated ASCVD by misclassifying people at various LDL-C target levels. Conclusion: There is a difference between direct LDL-C and c-LDL-C values in people with diabetes and this may result in misclassifying ASCVD especially at lower levels of LDL-C and higher levels of TGs.